1996
DOI: 10.1021/jf940643w
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Ascorbic Acid in the Presence of Nitrites

Abstract: We have shown that ascorbic acid in neutral aqueous media rather rapidly interacts with nitrite ions to form dehydroascorbic acid. If the acidity of solution is sufficiently high (pH value does not exceed much above ∼7) and the nitrite concentration is of order of 0.05 M or more, the only mechanism of the reaction under aerobic conditions includes, as the first, rate-limiting reaction step, the nitrosation of ascorbic acid. A second-order reaction kinetics was observed in respect to protons, which determined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…It has been reported that nitric oxide formation can be measured using an oxygen electrode [18–20]. As a mechanism of nitric oxide formation by AA/nitrite systems under acidic conditions, reduction of nitrous acid by AA is possible [5–9]: …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that nitric oxide formation can be measured using an oxygen electrode [18–20]. As a mechanism of nitric oxide formation by AA/nitrite systems under acidic conditions, reduction of nitrous acid by AA is possible [5–9]: …”
Section: Resultsmentioning
confidence: 99%
“…Saliva, which contains nitrite (0.05–0.2 mM) (p K a =3.3) [1,2], is normally swallowed into the stomach and mixed with gastric juice, which contains ascorbic acid (AA) (0.05–0.3 mM) [3,4], and it is well known that nitrite is reduced by AA, producing nitric oxide under acidic conditions [5–9]. According to these reports, it is supposed that nitric oxide is formed when saliva is mixed with gastric juice.…”
Section: Introductionmentioning
confidence: 99%
“…The results described here show that ascorbic acid may be a poor inhibitor of nitration or deamination by nitrite under acidic conditions such as those of the stomach. In neutral aqueous media, ascorbic acid reacts very slowly with nitrite, forming dehydroascorbic acid via a nitrosation reaction (32). The rate-limiting step is the formation of the nitrosating agent which is proposed to be either N 2 O 3 or H 2 NO 2 + (32).…”
Section: Discussionmentioning
confidence: 99%
“…The rate-limiting step is the formation of the nitrosating agent which is proposed to be either N 2 O 3 or H 2 NO 2 + (32). The reaction is highly pH-dependent, suggesting that nitrite accelerates vitamin C decay in fruit and vegetables under acidic storage conditions (32). Dahn et al (33) have observed that the rate of reaction between nitrite and ascorbic acid is slow at physiological concentrations of nitrite in acidic media due to the formation of N 2 O 3 .…”
Section: Discussionmentioning
confidence: 99%
“…There is little doubt that antioxidants effectively inhibit the formation of nitrosamines by scavenging nitrite (Shenoy and Choughuley 1992, Myshkin et al. 1996, Rundlöf et al.…”
Section: Discussionmentioning
confidence: 99%